Handbook of semiconductor manufacturing technology - Doering, Robert (CRC Press, 2008)
New to the second edition of this reference are sections on silicon-on-insulator (SOI) materials and devices, supercritical CO2 in semiconductor cleaning, low-'5f dielectrics, atomic-layer deposition, Damascene copper electroplating, and effects of terrestrial radiation on integrated circuits. The handbook contains 35 chapters, each containing an overview of as many key topics in the industry. The chapters present background, research-and-development issues, and future trends and are written so as to be accessible to the non-specialist as well as the specialists and students in the industry who will be the work's main audience. The range of chapter topics includes dopant diffusion, silicides, rapid thermal processing, atomic layer deposition, yield modeling, yield management, failure analysis, and factory modeling. Four appendices contain physical constants, units conversion, standards, and acronyms.